Innovation, sustainability and climate action: This is how the AgriLAC Resiliente initiative is progressing in Guatemala - Arce Gomez, Daniela; Borrayo, Andrea Surama (2025)
Within the CGIAR Scaling for Impact Science Program, the AgriLAC NORAD initiative is advancing in Guatemala by promoting innovations focused on sustainability and climate action in agri-food systems. Through participatory spaces for exchange and analysis, territorial and institutional actors have shared progress, lessons learned, and results from 2023 and 2024, with an emphasis on the adoption of climate-smart practices and gender and social inclusion approaches.